Facebook como herramienta de promoción y difusión audiovisual de contenidos culturales en el cantón Caluma - Cambo Chillo, Lady Galud (2020)
Within this research, a content analysis was carried out on the digital media of the Facebook social network of the Caluma canton, Bolívar province, during the year 2019, to determine the use of this network as a tool for the promotion and audiovisual dissemination of cultural contents of the mentioned area. The modality of this study was qualitative, through descriptive, diagnostic and exploratory research, through the direct observation technique supported by the observation record collection instrument. Among the findings, it was detected that there are few media such as: Municipality of Caluma, Caluma Bello, Caluma Tv.sa and Dúo Films, which were study subjects, where it was found that the production of videos in the studied media is not Also, the cultural theme is a content that is very little considered, concluding that the use of the aforementioned network as a tool for the promotion and dissemination of culture is bad, therefore it is recommended to maintain a communication strategy for audiovisuals on this platform , in addition to the communication students applying these strategies in their.